CONFLICT OVERCOMING IN THE "TEACHER-STUDENT" SYSTEM BY MEANS HUMANISTIC APPROACH TO THE ORGANIZATION PEDAGOGICAL PROCESS (Pedagogy of Higher and Secondary Education, 2006)
The possibilités of the humanistic approach to the organization of pedagogikal process in overcoming the conflict relations between the teacher and tne pupil are considered in this article.